Maternal exposure to glyphosate-based herbicide causes long-term changes in vascular relaxation from offspring adult rats (Research, Society and Development, 2021)
This study aimed to investigate whether exposure to glyphosate-based herbicide during the gestational phase promotes long-term effects on the vasomotor function of the thoracic aorta and the possible involvement of oxidative stress and cyclooxygenase II in these alterations. For this, in a isolated organ bath, the endothelium-dependent and independent relaxation of aortic rings of rats from mothers treated with glyphosate in the maternal phase (O-GHB) and tap water the control group (O-CON) were evaluated. Pharmacological tools such as L-NAME, TEMPOL and Indomethacin were used for investigate possible mechanisms. As a result, an impairment in vascular relaxation related to an endothelial dysfunction in O-GHB rats was observed. This endothelial dysfunction was reversed when the aortic rings were in the presence of superoxide dismutase and COX-2 mimetic, supporting the hypothesis that adverse effects during the intrauterine phase, such as oxidative stress caused by glyphosate, can lead to late changes in the function of some organs, in the case studied here, in vascular reactivity in the aorta.